2019
DOI: 10.1097/dcc.0000000000000384
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of HeartMath Resiliency Training on Health Care Providers

Abstract: Background Health care providers must think clearly and make critical decisions under stressful circumstances. Providing effective strategies for managing stress in the moment helps mitigate the physical, emotional, and psychological impacts associated with caring for others and promotes resiliency. Staff may also utilize these techniques with patients and their families to help alleviate the symptoms of stress that may be experienced as the result of illness. Aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“…[ 14 ] Another healthcare study used a pretest/posttest model and self-selected employees (including physicians and nurses) within an academic medical center; their results supported the stress-reducing and resilience-building effects of self-regulation with biofeedback. [ 15 ] Even though some studies have not observed any significant effectiveness of biofeedback,[ 13 ] studies looking at other high-stress professions had more promising and consistent results. For example, a study of combat veterans both with and without PTSD showed cognitive improvement after training in self-regulation and weekly HRV,[ 5 ] and an RCT demonstrated that pre-deployment self-regulation training resulted in lower post-deployment PTSD symptom scores.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] Another healthcare study used a pretest/posttest model and self-selected employees (including physicians and nurses) within an academic medical center; their results supported the stress-reducing and resilience-building effects of self-regulation with biofeedback. [ 15 ] Even though some studies have not observed any significant effectiveness of biofeedback,[ 13 ] studies looking at other high-stress professions had more promising and consistent results. For example, a study of combat veterans both with and without PTSD showed cognitive improvement after training in self-regulation and weekly HRV,[ 5 ] and an RCT demonstrated that pre-deployment self-regulation training resulted in lower post-deployment PTSD symptom scores.…”
Section: Discussionmentioning
confidence: 99%
“…These training participants included, e.g., nurses, residents, and physicians, coming from various disciplines and representing different hierarchical levels of the organization. Employees working in health administration and health management represented the target group in six studies (Grant et al, 2009;Pipe et al, 2012;van Agteren et al, 2018;Buchanan and Reilly, 2019;Heather et al, 2019). In contrast to frontline employees in health care, their work in administration does not include direct medical contact with patients.…”
Section: Target Groupmentioning
confidence: 99%
“…In contrast to frontline employees in health care, their work in administration does not include direct medical contact with patients. Four of these six studies, however-those by Buchanan and Reilly (2019) Eleven studies investigate employees working in high-risk environments that involve ensuring public safety and security, such as members of military services (Carr et al, 2013;de Visser et al, 2016;Fikretoglu et al, 2019), police officers (Arnetz et al, 2009;McCraty and Atkinson, 2012;Arble et al, 2017;Carleton et al, 2018;Christopher et al, 2018), firefighters (Joyce et al, 2018;, and disaster workers (Mahaffey et al, 2021).…”
Section: Target Groupmentioning
confidence: 99%
“…Based on surveys of 26 health care providers who participated, the program resulted in significant reductions in organizational (11 percent), emotional (24 percent), and physical (21 percent) stress. 11 Nurses should make a concerted effort to focus on the positive, such as taking notice when they have been kind to themselves or made others happy; and be intentional about noticing what brings them joy, both professionally and personally. Starting a gratitude journal to write down things for which to be grateful may be helpful for staying positive.…”
Section: For Individualsmentioning
confidence: 99%
“…With self-care, perfection should not be the goal; rather, a focus on small changes, such as refilling a water bottle on a different floor to take additional steps when time does not allow for a walk, can be beneficial mentally and physically. 11 Because one significant contributor to burnout is a feeling of powerlessness, nurses should focus on speaking up (e.g., about receiving regular breaks), getting involved throughout their facility when possible (e.g., attending meetings to represent the interests of the nurses, developing and sharing solutions to common problems), or pursuing educational opportunities (e.g., degree programs, requesting training on new tasks or equipment). 1…”
Section: For Individualsmentioning
confidence: 99%